1991
DOI: 10.1002/ana.410300512
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cardiomyopathy and weakness or acute coma in children with a defect in carnitine uptake

Abstract: A defect in intracellular uptake of carnitine has been identified in patients with severe carnitine deficiency. To define the clinical manifestations of this disorder, the presenting features of 15 affected infants and children were examined. Progressive cardiomyopathy, with or without chronic muscle weakness, was the most common presentation (median age of onset, 3 years). Other patients presented with episodes of fasting hypoglycemia during the first 2 years of life before cardiomyopathy had become apparent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(98 citation statements)
references
References 18 publications
4
92
0
2
Order By: Relevance
“…As in other previous studies, no genotype-phenotype relationship was observed. (Garavaglia et al 1991;Lamhonwah et al 2002;Li et al 2010;Longo et al 2006;Stanley et al 1991;Wang et al 2000aWang et al , b, 2001). Even siblings with the same mutation have different ages of onset and different progressions of disease pointing to the presence of clinical heterogeneity (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other previous studies, no genotype-phenotype relationship was observed. (Garavaglia et al 1991;Lamhonwah et al 2002;Li et al 2010;Longo et al 2006;Stanley et al 1991;Wang et al 2000aWang et al , b, 2001). Even siblings with the same mutation have different ages of onset and different progressions of disease pointing to the presence of clinical heterogeneity (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This case's serum carnitine level was higher than other cases (6.76 mmol/L). Identification of mutations in siblings is critical because of the progressive and lethal nature of this disorder and the high incidence of sudden unexpected infant deaths unless there is early diagnosis and prompt therapeutic intervention (Stanley et al 1991;Tein et al 1990). Free carnitine levels in the plasma before initiation of therapy were 2.63 AE 1.92 mmol/L (N: 10-60), after a year of therapy free carnitine levels in the plasma raised to 16.62 AE 5.11 (N: 10-60) (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Different types of presentation have been observed within an individual family. 17 In family Jer, two affected siblings homozygous for the R399Q mutation presented either early in life with hypoglycemic coma or with mild delays later in life. To our knowledge, this is the first time that a child with this disorder has presented with isolated developmental delays.…”
Section: Discussionmentioning
confidence: 99%
“…Many cases of human systemic carnitine deficiency have been reported [4][5][6][7]. Recently, more than 20 cases of human systemic carnitine deficiency have been shown to have a defect of carnitine uptake into cultured fibroblasts and are suspected to have impaired renal conservation of carnitine.…”
Section: Introductionmentioning
confidence: 99%
“…jvs, juvenile visceral steatosis; FBP, fructose 1,6-bisphosphate; GOT, glutamic oxaloacetic transaminase; SDH, succinate dehydrogenase; NCP, non-collagen protein. [5][6][7]. Unexpectedly, there have been only a few reports that give the detail informations about the cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%